Concurrent training in prepubertal children: An update - Alves, A. R.; Marta, C.; Neiva, H. P.; Izquierdo, M.; Marques, M. C. (Journal of Human Sport & Exercise, 2018)
This paper affords an update review over the state of art regarding the importance of physical fitness and the significance of different combination approaches between resistance and aerobic training, as well as conditioning methods exercise alone on physical fitness improvements, specifically explosive strength and cardiorespiratory fitness in prepubertal children. The main research conclusions can be summarized as: i) Resistance training can be reliable to improve muscle strength in prepubertal children; ii) A proper and quantifiable exercise frequency and intensity in aerobic training remains unclear; iii) No differences have been found between prepubertal girls and boys on strength and aerobic capacity improvements after intra-session concurrent training , resistance or aerobic training alone; iv) In adults, concurrent resistance and aerobic training seems to be more effective on improvements of aerobic capacity than aerobic training alone; v) Aerobic training biomechanically specific to the concurrent resistance training may minimize adaptation interference when concurrently training; vi) In adolescents, concurrent resistance and aerobic training is equally effective to improve explosive strength compared to resistance training alone, and more efficient in aerobic capacity than resistance training alone; vii) Optimum training sequence was determined by the individual purposes of the training program; viii) Performing aerobic prior to resistance training produces endurance gains, while performing resistance prior to aerobic training appears to be more adequate to obtain strength improvements; ix) In adults, performing concurrent training in different sessions seems to be more effective to improve muscular strength than intra-session concurrent training. These results can be helpful for coaches, teachers and researchers to optimize explosive strength and cardiorespiratory fitness training in sports club and school-based programs, as well as a reliable source for further researches.